Relationship between Open Unemployment Rate, Employment Opportunity Rate, Dependency Ratio and Economic Growth in Indonesia - Risdia Intan Fajarisa; Agus Sumanto; Inayati Nuraini Dwiputri (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
In this study, it analyzes the dynamics of employment in Indonesia before and during the Covid-19 pandemic. The COVID-19 pandemic has an impact on all sectors, especially the employment sector in Indonesia. This study used the variables of open unemployment rate, employment opportunity, dependency ratio and economic growth. This study used dynamic analysis with the vector error correction model (VECM) method with the research year 1987-2021. The results of this study explain that GDP has a long-term effect on changes in the value of the dependency ratio, the Employment Opportunity Rate has a coefficient of 430.7657 in Lag 1 which can be interpreted to mean that if there is an increase in the value of the Employment Opportunity Rate by 1% in the previous year, it will reduce the dependence ratio in the long term. the variable open unemployment rate has a coefficient of 430.6932 in Lag 1 which means that if there is an increase in the open unemployment rate of 1% in the previous year, it will increase the value of the dependency ratio in the long term. the relationship of GDP to the dependency ratio in the short term. The value of the GDP coefficient of 0.020050 in Lag 1, the figure explains that if the value of GDP increases by 1 percent in the previous year, it can encourage an increase in the value of the dependency ratio of 0.020050 percent in the current year.